2021
DOI: 10.1029/2020jd033339
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Record Arctic Stratospheric Ozone Depletion in 2020

Abstract: In the Arctic winter/spring of 2019/2020, stratospheric temperatures were exceptionally low until early April and the polar vortex was very stable. As a consequence, significant chemical ozone depletion occurred in the Arctic polar vortex in spring 2020. Here, we present simulations using the Chemical Lagrangian Model of the Stratosphere that address the development of chlorine compounds and ozone in the Arctic stratosphere in 2020. The simulation reproduces relevant observations of ozone and chlorine compound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 92 publications
2
17
0
Order By: Relevance
“…On the other hand, the Antarctic ozone column loss is about twice that of the Arctic (about 150-160 DU) but slightly lower (about 100-120 DU) in warm winters (1988 and 2002) and in early years (e.g. 1979-1985) of ozone loss there (Huck et al, 2005;Tilmes et al, 2006;Kuttippurath et al, 2015). The analyses suggest that even the partial column ozone loss in the Arctic winter of 2020 is about 115 DU at 350-550 K, which is higher than that of the Arctic winter of 2011 and similar to that of the loss found in the Antarctic winters of 1979-1985, 2002, and 2019. Since the ozone loss in the Arctic winter of 2020 is up to the levels of that found in some Antarctic winters, we examined the occurrence of extremely low TCO values using data from OMPS and MERRA-2; the results are presented in Dameris et al, 2021).…”
Section: Days With Ozone Values Below a Threshold Of 220 Dumentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the Antarctic ozone column loss is about twice that of the Arctic (about 150-160 DU) but slightly lower (about 100-120 DU) in warm winters (1988 and 2002) and in early years (e.g. 1979-1985) of ozone loss there (Huck et al, 2005;Tilmes et al, 2006;Kuttippurath et al, 2015). The analyses suggest that even the partial column ozone loss in the Arctic winter of 2020 is about 115 DU at 350-550 K, which is higher than that of the Arctic winter of 2011 and similar to that of the loss found in the Antarctic winters of 1979-1985, 2002, and 2019. Since the ozone loss in the Arctic winter of 2020 is up to the levels of that found in some Antarctic winters, we examined the occurrence of extremely low TCO values using data from OMPS and MERRA-2; the results are presented in Dameris et al, 2021).…”
Section: Days With Ozone Values Below a Threshold Of 220 Dumentioning
confidence: 89%
“…The peak ozone loss in the Antarctic happens at around 500 K, and the loss is severe from 400 to 600 K for 5 months continuously from August to November (Tilmes et al, 2006;Huck et al, 2005;Sonkaew et al, 2013;Kuttippurath et al, 2015;Kirner et al, 2015). In contrast, the cold Arctic winters are normally shorter and maximum ozone loss occurs at around 425-475 K for a period of about 2 months from mid-January to mid-March (e.g.…”
Section: The Arctic Ozone Loss and The Antarctic Ozone Lossmentioning
confidence: 99%
“…Previous studies have also reported high cloud formation in the lower stratosphere (between 50 and 200 hPa) in the Arctic both during the winter and summer seasons (Fadnavis et al, 2019;Cairo and Colavitto 2020). Arctic clouds in the stratosphere in winter (polar stratospheric clouds) occur because of low stratospheric temperatures (e.g., Grooß and Müller, 2021;Tritscher et al, 2021). During summer, the negative anomalies in the high cloud in the upper troposphere (300-150 hPa) may be associated with the transport of sulfate aerosols mostly occurring above the tropopause (Fadnavis et al, 2019).…”
Section: Impacts Of Sulfate Forcing On Cloudsmentioning
confidence: 98%
“…The quantitative estimation of ozone loss in the same air mass (as opposed to the accumulated loss in different air masses at a given pressure level discussed so far) in the winter 2019/2020 is covered in detail elsewhere (e.g., Feng et al, 2021;Grooß & Müller, 2021;Manney et al, 2020;Wohltmann et al, 2020), and we will only give a short comparison of our results to other studies. The maximum in the simulated ozone loss profile averaged over the vortex obtained with a passive ozone tracer (see Wohltmann et al, 2020) Manney et al (2020) give a value of 2.8 ppm for the MLS match approach and a vortex-averaged descent approach.…”
Section: Ozone Loss Estimates In the Same Air Massmentioning
confidence: 99%